2011
DOI: 10.1143/jjap.50.09mf01
|View full text |Cite
|
Sign up to set email alerts
|

Sixteen-Layer Write Once Disc with a Separated Guide Layer

Abstract: We proposed a new recordable multilayer optical disc and its recording system. The new optical disc has multiple-plane-recordable layers and a separated guide layer, and we fabricated 16 recording layers made of high-transmittance inorganic recording materials stacked on the separated guide layer. The recorded signals were evaluated on all recording layers by using jitter and i-MLSE as the evaluation indicators. As a result, the technical feasibility of our proposal was confirmed to achieve the total capacitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…To lighten the manufacturing burden, we have already proposed the separated guide layer concept to simplify the disc structure and confirmed the technical feasibility of realizing the recording capacity of 512 GB. 21,22) In this paper, we introduced the advanced radial position control system for a super multilayer disc with the separated guide layer, which consists of an advanced sled servo system and a specially designed APP optics. We confirmed that the proposed system realized stable recording on the plane recording layer located far from the guide layer, with a constant track pitch of 0.32 m, the same as that of BD discs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To lighten the manufacturing burden, we have already proposed the separated guide layer concept to simplify the disc structure and confirmed the technical feasibility of realizing the recording capacity of 512 GB. 21,22) In this paper, we introduced the advanced radial position control system for a super multilayer disc with the separated guide layer, which consists of an advanced sled servo system and a specially designed APP optics. We confirmed that the proposed system realized stable recording on the plane recording layer located far from the guide layer, with a constant track pitch of 0.32 m, the same as that of BD discs.…”
Section: Discussionmentioning
confidence: 99%
“…To lighten the manufacturing burden, we proposed the separated guide layer concept to simplify the disc structure and confirmed the technical feasibility to realize a recording capacity of 512 GB. 21,22) In our multilayer recording system, the radial position of a recording beam on the plane recording layer is controlled by using another one on the separated guide layer, called a guide beam. Therefore, there is a concern that the recorded track pitch will deviate owing to the difference in optical axis between the two laser beams.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this type of disc and system, i.e., the separated guide groove system, has been proposed. 5,25) Our multilayer disc is supposed to be used in such a system.…”
Section: Fabrication Processes For Multilayer Discsmentioning
confidence: 99%
“…Several studies on the technology of high-capacity optical discs, for example, multilayer optical discs, [1][2][3][4][5][6] holographic memories, 7,8) solid immersion lenses, 9,10) superresolution near-field structures (super-RENS), 11,12) and flexible discs, 13,14) have been reported. In particular, the multilayer optical disc is the most promising technology for realizing high-capacity storage devices because it can utilize Blu-ray disc (BD) technology for its basic system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation